Back Cover: Bottom‐Up Formation of Dodecane‐in‐Water Nanoemulsions from Hydrothermal Homogeneous Solutions (Angew. Chem. Int. Ed. 25/2013). Issue 25 (5th June 2013) - Deguchi, Shigeru; Ifuku, Nao
<x xml:space="preserve">Abstract</x> In the deep oceans at tectonically active areas, hot and compressed water, sometimes in the supercritical state, gushes out from the sea floor. The water is rapidly cooled to near‐freezing temperature by surrounding cold water. Such a unique environment in the deep ocean inspired S. Deguchi and N. Ifuku to develop a novel bottom‐up emulsification process, described in their Communication on page 6409 ff. The photograph (© JAMSTEC) shows a hydrothermal activity at the depth of 1492 m near Ryukyu Islands, Japan.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>